Naegleria fowleri: An emerging drinking water pathogen. Issue 10 (1st October 2014) - Bartrand, Timothy A.; Causey, Jonathan Jake; Clancy, Jennifer L.
Abstract : Naegleria fowleri (N. fowleri) is a free‐living, trophic amoeba that is nearly ubiquitous in the environment and can be present in high numbers in warm waters. It is the causative agent of primary amoebic meningoencephalitis (PAM), a rare but particularly lethal disease with a very low survival incidence. Although N. fowleri was isolated from drinking water supplies in Australia in the 1980s, it was not considered a drinking water threat in the United States until recent cases were associated with a groundwater system in Arizona and surface water systems in Louisiana. N. fowleri in drinking water treatment and distribution systems can be managed using disinfectant concentrations typically encountered in well‐run plants although nitrification and attendant low disinfectant residuals may pose a challenge for some systems. The greatest challenge for N. fowleri control is in premise plumbing systems where conditions are largely outside the control of utilities, residuals might be low or nonexistent, and where water temperatures could be high enough to support rapid growth of the amoebae. This article reviews published studies describing the environmental occurrence, survival, pathogenicity, and disinfection of N. fowleri. In addition, this article provides information about this little known and poorly understood parasite with respect to its occurrence in the environment; how the amoeba amplifies in water systems such that it can cause infection; how N. fowleri has been successfully controlled for decades in water systems through treatment and distribution system management in Australia; and the knowledge gaps and information needed to address N. fowleri as an emerging pathogen in US water supplies.